On the Move to Meaningful Internet Systems, OTM 2010 Confederated International Conferences: CoopIS, IS, DOA and ODBASE, Hersonissos, Crete, Greece, October 25-29, 2010, Proceedings, Part II - Meersman, Robert; Dillon, Tharam; Herrero, Pilar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The two-volume set of LNCS 6426/6427 constitutes the refereed proceedings of 3 confederated international conferences on CoopIS (Cooperative Information Systems), DOA (Distributed Objects and Applications) and ODBASE (Ontologies, DataBases and Applications of SEmantics). These conferences were held in October 2009 in Greece, in Hersonissos on the island of Crete. CoopIS is covering the applications of technologies in an enterprice context as workflow systems and knowledge management. DOA is covering the relevant infrastructure-enabling technologies and finally, OSBASe is covering WEB semantics, XML databases and ontologies. The 83 revised full papers presented together with 3 keynote talks were carefully reviewed and selected from a total of 223 submissions. Corresponding to the OTM main conferences the papers are organized in topical sections on process models and management, modeling of cooperation, services computing, information processing and management, human-based cooperative systems, ontology and workflow challenges, access control, authentication and policies, secure architectures, cryptography, data storage and processing, transaction and event management, virtualization performance, risk and scalability, cloud and distributed system security, reactivity and semantic data, ontology mapping and semantic similarity, domain specific ontologies.
On the Move 2010 Keynotes -- OTM$1 (B10 Keynote -- OTM$1 (B10 Keynote -- Distributed Objects and Applications (DOA) International Conference 2010 -- DOA$1 (B10 - PC Co-chairs Message -- Data Storage and Processing -- Data Stream Analytics as Cloud Service for Mobile Applications -- On the Expressiveness and Trade-Offs of Large Scale Tuple Stores -- Context-Aware Tuples for the Ambient -- Transaction and Event Management -- Overlay Routing under Geographically Correlated Failures in Distributed Event-Based Systems -- Scalable Transactions in the Cloud: Partitioning Revisited -- Fadip: Lightweight Publish/Subscribe for Mobile Ad Hoc Networks -- Virtualization Performance, Risk and Scalability -- Analysis of the Performance-Influencing Factors of Virtualization Platforms -- Measuring Software Systems Scalability for Proactive Data Center Management -- Semantic Similarity Model for Risk Assessment in Forming Cloud Computing SLAs -- Cloud and Distributed System Security -- A Distributed and Privacy-Preserving Method for Network Intrusion Detection -- Enforcing UCON Policies on the Enterprise Service Bus -- Detecting Sybil Nodes in Static and Dynamic Networks -- Ontologies, DataBases, and Applications of Semantics (ODBASE) International Conference 2010 -- ODBASE$1 (B10 - PC Co-chairs Message -- Invited Talks -- Wikabularies and the Like - Community-Based Knowledge Resources on the Web -- Personalization, Socialization, Contextualization: Preferences and Attitudes for Advanced Information Provision -- Annotations -- Integrating Keywords and Semantics on Document Annotation and Search -- A Context-Based Model for the Interpretation of Polysemous Terms -- Automatic Web Page Annotation with Google Rich Snippets -- A Hybrid Approach to Constructing Tag Hierarchies -- Inconsistencies -- Toward a Uniform Cause-Based Approach to Inconsistency-Tolerant Database Semantics -- Identifying and Eliminating Inconsistencies in Mappings across Hierarchical Ontologies -- Towards Evaluating GRASIM for Ontology-Based Data Matching -- Reactivity and Semantic Data -- Expressing and Managing Reactivity in the Semantic Web -- Onto-DIY: A Flexible and Idea Inspiring Ontology-Based Do-It-Yourself Architecture for Managing Data Semantics and Semantic Data -- Ontology Mapping and Semantic Similarity -- Save Up to 99% of Your Time in Mapping Validation -- XML-SIM-CHANGE: Structure and Content Semantic Similarity Detection among XML Document Versions -- Ontology-Driven Possibilistic Reference Fusion -- Towards Duplicate Detection for Situation Awareness Based on Spatio-temporal Relations -- Ontology Mapping and SPARQL Rewriting for Querying Federated RDF Data Sources -- A Semantic Similarity Framework Exploiting Multiple Parts-of Speech -- Domain Specific Ontologies -- Biomedical Publication Knowledge Acquisition, Processing and Dissemination with CORAAL -- Assessing Iterations of an Automated Ontology Evaluation Procedure -- OMIT: Domain Ontology and Knowledge Acquisition in MicroRNA Target Prediction.s
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information systems; Artificial intelligence; Information Systems; Computer Science; Computer Communication Networks; Software Engineering; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems